Cellular concrete-supported cost-effective adsorbents for aqueous arsenic and heavy metals abatement; Journal of Environmental Chemical Engineering; Vol. 5, iss. 4 - Martemyanov D. V. Dmitry Vladimirovich; Xie Binbin; Yurmazova T. A. Tatyana Aleksandrovna; Khaskelberg M. B. Mikhail Borisovich; Wang Fengli; Wei Chaohai H.; Preys S. Sergey (2017, 2017)
Title screen